Bone morphogenetic protein 4 signaling regulates development of the anterior visceral endoderm in the mouse embryo - Soares, Miguel L. (2008)
The extraembryonic ectoderm (ExE) of the mouse conceptus is known to play a role in embryo patterning by signaling to the underlying epiblast and surrounding visceral endoderm. Bmp4 is one of the key ExE signaling molecules and has been recently implicated to participate in regulating development and migration of the anterior visceral endoderm (AVE). However, it remains unclear when exactly BMP4 signaling starts to regulate AVE positioning. To examine this, we have chosen to affect BMP4 function at two different time points, at embryonic day 5.25 (E5.25), thus before AVE migration, and E5.75, just after AVE migration. To this end, an RNAi technique was used, which consisted of the injection of Bmp4 dsRNA into the proamniotic cavity of the egg cylinder followed by its targeted electroporation into the ExE. This resulted in specific knockdown of Bmp4. It was found that Bmp4 RNAi at E5.25, but not at E5.75, led to an abnormal pattern of expression of the AVE marker Cerberus-like. Thus, BMP4 signaling appears to affect the expression of Cer1 at a specific time window. This RNAi approach provides a convenient means to study spatial and temporal function of genes shortly after embryo implantation.